Mirizzi Syndrome. Issue 1 (1988) - Bower, Thomas C.; Nagorney, David M.
Abstract : The Mirizzi syndrome refers to benign obstruction of the common hepatic duct by a stone impacted within the neck or cystic duct of the gallbladder, which causes extrinsic compression of the common hepatic duct and obstructive jaundice. Although a rare cause of obstructive jaundice, it remains a clinically and surgically challenging problem. Five patients with the Mirizzi syndrome were culled from over 9000 patients undergoing operation for gallstone disease. The management of these patients was detailed. Diagnosis requires a high index of clinical suspicion but can be confirmed with the use of ultrasonography and percutaneous transhepatic cholangiography. Cholecystectomy and common duct exploration are essential components of operative therapy, but additional procedures to repair non-circumferential bile duct defects or strictures must be anticipated.